2015
DOI: 10.3748/wjg.v21.i10.3132
|View full text |Cite
|
Sign up to set email alerts
|

Primary hepatic neuroendocrine tumor with multiple liver metastases: A case report with review of the literature

Abstract: We herein present a case involving a 41-year-old woman in whom ultrasound examination revealed multiple liver hemangiomas more than 3 years ago. Follow-up ultrasound examination revealed that the masses had significantly increased; the largest was located in the right lobe (about 8.2 cm × 7.4 cm × 6.0 cm). Abdominal multidetector computed tomography revealed multiple well-circumscribed, heterogeneous, hypodense masses (largest, 6.4 cm × 6.3 cm × 5.0 cm) with significant contrast enhancement during the arterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 23 publications
1
29
0
2
Order By: Relevance
“… 14 , 15 The most common symptoms found in this study were right upper quadrant palpable mass and abdominal pain in both our cases and previous reports. 16 No patient with carcinoid syndrome was found, which agreed with a report that carcinoid syndrome was usually caused by metastatic neuroendocrine tumors. 17 …”
Section: Discussionsupporting
confidence: 90%
“… 14 , 15 The most common symptoms found in this study were right upper quadrant palpable mass and abdominal pain in both our cases and previous reports. 16 No patient with carcinoid syndrome was found, which agreed with a report that carcinoid syndrome was usually caused by metastatic neuroendocrine tumors. 17 …”
Section: Discussionsupporting
confidence: 90%
“…Diagnosis of PHNECs is considered challenging in view of the common initial presentation of GEP NECs as metastatic liver lesion. Hepatic neuroendocrine cell may originate from intrahepatic bile duct epithelial cells, heterotopic pancreatic cells, or adrenal tissue [ 4 , 5 ]. PHNECs can secrete a variety of polypeptides and biogenic amines, including 5-HT, pancreatic polypeptides, gastrin, prostaglandin, and calcitonin.…”
Section: Discussionmentioning
confidence: 99%
“…Highly differentiated NETs of grades G1 and G2 are considered benign, and poorly differentiated NETs of grade G3 are named neuroendocrine carcinoma. Studies in the literature have reported that 45% of NETs originate from the small intestine, 20% from the rectum, 17% from the appendix, 11% from the colon, and 7% from the stomach [4] . The liver is the most common metastatic organ of NETs, but PHNEC is rare, accounting for only 0.3-4.0% of all NETs [1] .…”
Section: Discussionmentioning
confidence: 99%
“…Primary hepatic neuroendocrine tumors (PHNETs) frequently stem from intrahepatic bile duct epithelial cells, adrenal tissue, or ectopic pancreatic cells [5] . PHNEC usually occurs in the right lobe of the liver.…”
Section: Discussionmentioning
confidence: 99%